Sensing-to-Sky Intermittent Connectivity Realization for LTE-Enabled Drone Platforms: Embedded Design, Measurement Study, and Positioning Applications - Kim, Junyoung; Jo, Uhyeong; Kim, Taewoon; Jung, Soyi; Kim, Joongheon (IEEE Access, 2024)
This paper presents practical scenarios for drone-based networking systems, specifically focusing on LTE-capable sensor-to-drone intermittent transmission over cellular networks. The proposed scenarios consider power limitations and connectivity instability inherent in drone operations. To validate the usability of these scenarios and networking architectures, an embedded system design and implementation using Reverse secure shell (SSH) is considered and realized. Real-world prototyping and implementation of the embedded system are conducted, followed by measurement studies to assess the feasibility of the proposed sensing-to-sky connectivity system. Furthermore, one of major applications for the system is introduced for the validation, i.e., optimal drone placement and positioning. The performance evaluation results confirm the practicality and effectiveness of the proposed approach for achieving intermittent communications between drones and ground-based systems over LTE networks. The findings contribute to advancing the field of drone networking and provide valuable insights for developing reliable and efficient sensing-to-sky communication systems.
Keywords: Aerial vehicle; Connectivity; Design measurements; Embedded designs; Embedded-system; Intermittent connectivity; Measurement study; Networking systems; Sensing; Unmanned aerial vehicle; connectivity; Drone; embedded system; sensing; unmanned aerial vehicle (UAV)